Fundamentals of Entrepreneurship (ENT300) : Kek Lapis Warisan / Mohd Shahlan Kassim... [et al.] - Kassim, Mohd Shahlan; Slidin, Wallter Panggau; Samsudin, Noor Izyan; Shaari, Regina; Zakaria, Azizah (2007)
Kek Lapis Warisan is the company that involves in manufacture and selling layer cakes. Our products are more likely Kek Lapis Sarawak which has various and unique design. The cakes are one of traditional handcraft introduced by the old generation of Sarawak. It is a heritage that needs to be continued by the new generation. Together with the forming of this company we came out with the name of Kek Lapis Warisan. We choose the name because it is symbol to our product whereby in English 'Warisan' mean heritage. We believe nowadays, the people are busy with their work and have not enough time to make preparation for the festive such as 'Hari Raya', Chinese New Year, Christmas, Gawai and so forth. With the existence of our company will help them to lighten their burden in term of preparation of cakes on those days Furthermore, they surely delighted to buy our products as the cakes are fully decorated with unique design and various flavors. For the local customer, they will proudly present the cakes to the outsider and persuade them to buy it as a souvenir.